Efeito da vaporização de toras e de madeira serrada na qualidade da secagem e na durabilidade biológica de hevea brasiliensis (Willd. ex Adr. de Juss.) Müll. Arg - Rodrigues, Paula Lúcia Martins [UNESP] (2012)
The wood of the rubber tree (Hevea brasiliensis) after a decline in latex production has the potential to be destined to furniture industry. Log steaming and steaming prior to drying (pre-steaming) are techniques used for improving the quality of wood. The present study evaluates the effect of these techniques in the variables related to the quality of the rubber tree wood, among them: drying rate, drying defects and biological durability. For this, it was used 18 rubber trees; from each tree, 2 logs were removed, totalizing 36 logs. At first, 18 logs from 18 trees were submitted to log steaming during 36 hours at a temperature of 90ºC and 100% relative humidity, while the other part was kept untreated. Then, every log were cut into band saw; half of the number was subjected to steaming prior to drying under saturated steam at 90°C for 3 h after 1 h of heating-up, while the other half was kept in its original condition. All flat sawn boards were dried in a kiln. The drying rate, warping and cracks were evaluated during this process. Finally the samples of juvenile and mature wood from 5 central boards of different trees were submitted to the accelerated test decay called soil-block to evaluate the durability to white-rot fungus Pycnoporus sanguineus. The results showed that: (1) the log steaming, the steaming prior to drying and the combination of these treatment did not promote significant effects on the drying rate of boards from rubber trees; (2) all levels of steaming applied in this study did not promote significant effects on the boards crack and warp indexes during the drying process; (3) the log steaming, the pre-streaming and the combination of these treatments promoted significant increases in the mass losses of 7.1%, 10.3% e 10.3% for juvenile wood respectively, and of 23.4%, 15.2% e 27.3% respectively for mature wood of ...